Social Media Marketing and E-Wom: Driving Purchase Intentions Through Brand Image - Maulidiah Winda Hani Syach; Dita Puruwita; Nofriska Krissanya (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2024)
The purpose of this research is to identify the factors influencing the purchase intention of Circle K products in the DKI Jakarta area, focusing on the variables of social media marketing, Electronic Word of Mouth (E-WOM), and brand image. The research uses a quantitative approach with the Structural Equation Model (SEM). Primary data was collected through questionnaires using a Likert scale ranging from strongly agree to strongly disagree. A purposive sampling method was used to obtain the sample, and the researchers gathered data from 210 respondents. The results of the study indicate that social media marketing and E-WOM have a positive and significant direct impact on brand image. Purchase intention also has a positive and significant direct impact on brand image. Additionally, social media marketing and E-WOM positively and significantly influence purchase intention through brand image. However, social media marketing and E-WOM do not have an impact on purchase intention. Keywords: purchase intention, brand image, social media marketing, electronic word of mouth, and Circle K